THE PHYSICAL FITNESS LEVEL OF STUDENTS WHO PRACTICE AND DON´T PRACTICE CAPOEIRA (Fiep Bulletin - online, 2013)
This study analyzes the physical fitness of 16 public school students between the ages of 10 and 15, eight of whom practice capoeira and eight of whom do not. Tests were carried out among the participants measuring power and resistance of the upper members and lower members, agility, reaction speed, balance, and localized strength resistance. The findings revealed higher levels of physical fitness among the practitioners of capoeira. As part of the school curriculum, capoeira impacts a student's overall development.
Keywords: Physical Fitness; Capoeira; Scholastic Physical Education